Sociodemographic Indicators of Birth Rate in a Low Fertility Country–A Nationwide Study of 310 Finnish Municipalities Covering > 5,000,000 Inhabitants - Oura, Petteri (Frontiers in Public Health, 2021)
Background and Aims: Declining fertility is a key driver behind the rapid aging of populations worldwide. Finland has experienced a 25% decline in fertility from 2010 to date and ranks low even on the European and Nordic scales. This study aimed to address the association between sociodemographic indicators and birth rate (i.e., live births relative to total population) in Finland. Methods: Open data on 310 Finnish municipalities were retrieved from the public database of Statistics Finland. Several sociodemographic subdimensions (population structure, education and income, location and living, divorces, car ownership rate, and crime rate), each converted to standard deviation units, were modeled against birth rate at the municipality level using generalized estimating equations. Results: In this dataset, average annual birth rate was 8.8 per 1,000 individuals. Birth rate was positively associated with change in population size (rate ratio 1.06, 95% confidence interval 1.04−1.08), percentage of <15-year-olds (1.29, 1.22−1.36), percentage of individuals living in their birth municipality (1.05, 1.03−1.08), and percentage of foreign language speakers (1.02, 1.01−1.04). In contrast, birth rate was negatively associated with percentage of ≥65-year-olds (0.90, 0.85−0.96), percentage of unemployed individuals (0.98. 0.95−0.99), income (0.92, 0.89−0.96), and number of individuals living in the same household unit (0.94, 0.90−0.98). Conclusion: The present findings are expected to advance the allocation of resources to areas and subpopulations that have high or low birth rate, and thus contribute to the development of a more family-friendly society. Future studies are encouraged to evaluate the sociodemographic indicators of birth rate in other low fertility countries, and to address the individual-level mechanisms behind the municipality-level associations identified in this study.